Effect Of Manual Traction Physotherapy On Knee Injury And Osteoarthritis Outcome Score And Interleukin-6 Levels In Patient Knee Osteoarthritis - Waode Riska Astuti Aini; Dedi Ardinata; Milahayati Daulay (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Knee osteoarthritis (OA) is the most common degenerative joint disease with a high global prevalence. It causes pain, joint stiffness, muscle weakness, and reduced functional activity, significantly affecting patients' quality of life. Inflammatory factors, particularly interleukin-6 (IL-6), play a role in the pathogenesis of knee OA, contributing to inflammation and pain sensitization. Non-pharmacological management of knee OA includes physiotherapy manual traction therapy, aimed at reducing pain and improving joint function. However, the relationship between manual traction and the reduction of IL-6 levels as well as improvements in the Knee Injury and Osteoarthritis Outcome Score (KOOS) has not been widely studied. Objective: To analyze the effect of physiotherapy manual traction on KOOS values and serum interleukin-6 (IL-6) levels in patients with knee osteoarthritis. Methods: This experimental study used a pre-post test design involving 36 patients with knee OA who received manual traction interventions twice a week for four weeks. KOOS values and IL-6 levels were measured before and after the intervention. Data were analyzed using the Wilcoxon test and Spearman correlation. Results: A significant increase in KOOS scores was observed after the intervention (p = 0.001), but no significant reduction in IL-6 levels was found (p = 0.491). The correlation between changes in IL-6 levels and KOOS scores was very weak and not statistically significant (r = 0.122; p = 0.760). Conclusion: Manual traction physiotherapy significantly improves knee joint function and quality of life in patients with knee OA, but does not significantly reduce serum IL-6 levels over a short intervention period. Moreover, the correlation between changes in IL-6 and KOOS scores is very weak and not statistically significant